The influence of audience’s regulatory focus on the persuasive effect of different pro-vaccine messages - Dengke Xia; Yue Su; Mengyao Song; Tingshao Zhu; Nan Zhao; Hongwei Sun (PLoS ONE, 2025)
The aim of this study was to investigate the influence of an audience’s regulatory focus on the persuasive effect of different pro-vaccine messages. Study 1 (N = 169) examined attitude changes among audiences with different regulatory focus after reading pro-vaccine messages, and Study 2 (N = 201) added the exploration of message persuasiveness and vaccination intentions as well. The results of Study 1 and Study 2 showed that both high promotion fucus and high prevention focus could facilitate the attitude change elicited by messages emphasizing vaccine safety, official position and credibility. Meanwhile, high-promotion individuals were also more easily influenced by messages highlighting the benefits of vaccination, while high-prevention individuals were more receptive to messages focusing on the personal responsibility. Similar results also appeared when measuring perceived persuasiveness as dependent variable. However, these impacts of regulatory focus did not remain statistically significant on behavioral intention for most messages, except for the messages emphasizing vaccine effectiveness. The behavioral intention changes after reading these messages were significantly promoted by high promotion focus. Our findings could shed some light on the mechanism underlying personalized persuasion as well as more targeted vaccination promotion strategies.